Integrating the Project-Based Learning Model as An Effort to Strengthen the Pancasila Student Profile and Students’ Holistic Character - Ansori; Bagus Cahyanto; Fatik Lutviana Anggraini (STAI At-Tahdzib, 2025)
In the era of 21st century educational transformation, schools are required not only to produce academically intelligent students, but also to have strong character, national values, and skills that are relevant to global challenges. One of the strategic efforts to realize this is through the implementation of Project-Based Learning (PjBL) which is in line with strengthening the Pancasila Student Profile (P5). This study aims to analyze the implementation of the PjBL model in shaping students’ holistic character and developing 21st century skills at Alifya Elementary School Bondowoso in 2025. The approach used is qualitative with a descriptive method. Data was collected through classroom observations, in-depth interviews with teachers and students, and document analysis and project documentation. Data analysis is carried out through the stages of data reduction, data presentation, and interactive conclusion drawn. The results of the study show that the implementation of PjBL at Alifya Elementary School Bondowoso is carried out systematically through contextual projects such as the creation of miniature villages and mini parks that foster the value of mutual cooperation, responsibility, and creativity. The project activities also strengthen the dimensions of the Pancasila Student Profile, including faith and noble character, independence, cooperation, critical reasoning, and creativity. In addition, 21st century skills such as critical thinking, collaboration, communication, and creativity are developing significantly through planning activities, teamwork, problem-solving, and presentation of results. These findings confirm that PjBL not only improves cognitive achievement, but also shapes the moral, social, and spiritual character of students as a whole. Thus, the implementation of PjBL is an effective strategy in realizing the goal of national education based on Pancasila values in elementary schools.